A novel and unexpected one pot synthesis of pyrrolo[1, 2-a]quinolines. (25th May 2022) - Sansom, Geraud N.; Semken, Jessica; Kelso, Michael J.; Richardson, Christopher
Graphical abstract: Highlights: New low temperature intramolecular SNAr pathway to pyrrolo[1, 2- a ]quinolines. Temperature-dependent divergent mechanistic pathway. Structure analysis via single crystal X-ray crystallography. Abstract: A new low temperature route to pyrrolo[1, 2- a ]quinolines bearing ester groups in the 5-position is reported. The reaction mechanism was found to depend on the reaction temperature. At low temperatures it is proposed the reaction proceeds though an addition-intramolecular SN Ar-elimination pathway. This method should find wider use as it avoids high boiling point solvents and affords compatibility with thermosensitive substrates.